Measuring perceived fitness interdependence between humans and non-humans - Lee, K; Hare, D; Blossey, B (Cambridge University Press, 2024)
Conservation ethics (i.e. moral concern for non-human organisms) are widespread, but we lack a comprehensive explanation for why people care about other species at all, and why they express strong moral concern for some species but not others. Recent theory suggests that conservation ethics might be rooted in cooperation between humans and members of other species. Building on central predictions of this eco-evolutionary theory, we conducted an online study (N = 651) and exploratory factor analysis to develop two scales that independently measure perceived fitness interdependence (PFI) and conservation ethics. The PFI scale measures perceived shared fate as a proximate indicator of human fitness interdependence with non-human organisms (i.e. the degree to which humans and other organisms influence each other's evolutionary success, that is, survival and reproduction). We designed the conservation ethics scale to measure moral beliefs and attitudes regarding those organisms. Both scales are composed of two factors and demonstrate good internal reliability. By combining insights from various branches of the evolutionary human sciences, including evolutionary anthropology, evolutionary psychology and human behavioural ecology, we offer empirical tools to investigate eco-evolutionary foundations of conservation ethics and behaviour.